Occult transethmoidal encephalocele with Chiari I malformation leading to recurrent meningitis – An unusual presentation - Mandepudi, Sai Monika; Abburi, Anil Kumar; Dasari, Ravi Kiran; Sadasiveni, Krishna Raja (Indian Journal of Case Reports, 2026)
Transethmoidal encephalocele, as a non-traumatic variant, is a rare subtype of basal encephaloceles, characterized by herniation of meninges and brain tissue through defects of the cribriform plate or ethmoid roof. It may present in adulthood with persistent postnasal drip, cerebrospinal fluid rhinorrhea or recurrent meningitis, and can be easily overlooked. Chiari I malformation is characterized by caudal descent of the cerebellar tonsils through the foramen magnum and may or may not be associated with a syrinx. Transethmoidal encephalocele and Chiari malformation can coexist and can be the preceding factor for the other. We report a case of occult transethmoidal encephalocele with cerebellar descent and cervical cord syrinx presenting with recurrent meningitis in an 18-year-old patient